2010
DOI: 10.1590/s1807-59322010000900010
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary metastasectomy from soft tissue sarcomas

Abstract: INTRODUCTION:Isolated pulmonary metastases from soft tissue sarcomas occur in 20-50% of these (the issue is about metastases, not lung cancer) patients, and 70% of these patients will present disease limited only to the lungs. Surgical resection is well accepted as a standard approach to treat metastases from soft tissue sarcomas isolated in the lungs, and many studies investigating this technique have reported an overall 5-year survival ranging from 30-40%. The most consistent predictor of survival in these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 35 publications
0
44
1
4
Order By: Relevance
“…3 However, some other studies did not prove any association between the number of metastases and patient survival. 18 We found a relatively lower success rate and lower overall survival rate in patients with a higher number of metastases (>2 vs. 1-2), but the difference did not reach statistical significance. We did not find any significant correlation between the size of metastasis and survival, although some studies suggested that larger size of metastasis resulted in poorer outcomes.…”
Section: Discussioncontrasting
confidence: 64%
“…3 However, some other studies did not prove any association between the number of metastases and patient survival. 18 We found a relatively lower success rate and lower overall survival rate in patients with a higher number of metastases (>2 vs. 1-2), but the difference did not reach statistical significance. We did not find any significant correlation between the size of metastasis and survival, although some studies suggested that larger size of metastasis resulted in poorer outcomes.…”
Section: Discussioncontrasting
confidence: 64%
“…There was one retrospective cohort study of data obtained from a Cancer Centre's institutional Tumor Registry 11. In other reports, cases were identified from databases which were held, as far as we could determine, at an institutional level10 12–17 20 23 26 27 or departmental level 18 19 21 24 25. It appears that many of the clinical data were retrieved by retrospective case note review.…”
Section: Resultsmentioning
confidence: 99%
“…In individual instances authors specified that there should be no mediastinal or chest wall involvement;17 absence of pericardial or pleural effusions;12 that the overall operative risk was acceptable;26 or that there was no other available more effective treatment 19. In one report, increased size on chemotherapy was allowable, but not an increase in the number of metastases 24.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sardenberg et al (39) evaluated the treatment of patients with non-lung primary tumors. The authors concluded that pulmonary metastasectomy is a safe and potentially curative procedure for such patients, and that select patients can achieve long-term survival after lung resection.…”
Section: Infectious Diseasesmentioning
confidence: 99%